(untitled) (Journal of Global Arts Studies, 2025)
Background： Integrating the dialectics of nature and green ecology into residential space design is crucial for sustainable development. The dialectics of nature, as a scientific methodology, combined with the practical concerns of green ecology, profoundly impacts many fields. Applying these concepts to curriculum reform is vital for nurturing talent, advancing the industry, and fostering the harmonious coexistence of humanity and nature. Objective： To integrate natural dialectic thinking and green ecological concepts into residential space design, we’ll reform the curriculum, teaching, and practical aspects. The goal is to cultivate students’ problem-solving abilities using dialectical thinking and enhance their awareness and skills in green ecological design. Methods： Utilizing a Marxist view of nature, this research employs a multi-method approach: literature review to establish the theoretical framework, case studies to deconstruct practical applications, and practice-based research to identify industry needs and current teaching practices. Results： The reform of green eco-concept curriculum enhances students’ eco-design ability, and verifies the effectiveness of teaching transformation driven by natural dialectic thinking. Conclusion： The natural dialectic provides methodological support for the curriculum, constructs an organic integration mechanism of “theoretical cognition - technical practice - dialectical reflection”, and supports the cultivation of sustainable design talents with scientific rationality and philosophical discursive ability.